Covid, the Environment and Food Systems: Contain, Cope and Rebuild Better - Markandya, Anil; Salcone, Jacob; Hussain, Salman; Mueller, Alexander; Thambi, Simi (Frontiers in Environmental Science, 2021)
The objective of this paper is to analyse impacts of COVID-19 on the nexus of food systems, the environment and sustainable development and propose ways for governments and international agencies to mitigate impacts in the short and medium term. It covers the historic period from early 2020 to early 2021 and also makes an assessment on future prospects. Although evidence is collected from all around the world, the focus is primarily on developing countries. The methods used are a review of the announced actions and preliminary findings in the academic and grey literature as well as on reliable websites from global and international institutions. By October 2020, governments around the world had invested about 12 trillion to counteract the economic effects of COVID-19. This investment could contribute to progress on the SDGs and global climate targets insofar as it was invested within a framework that supports both socio-economic recovery and sustainability. Initial analysis indicates that investments for economic recovery did not sufficiently address food security and sustainability, concentrating instead on immediate economic risk management. The global sustainable development agenda must promote the resilience and sustainability of food systems through policies and measures that: (i) account for environmental thresholds and trade-offs; (ii) promote food security and healthy diets; (iii) enhance and protect rural livelihoods; and (iv) address the inequalities and injustices that have emerged and will prevail during a post-COVID transition. National stimulus programs and the actions of international agencies must be assessed and monitored to deliver multiple benefits simultaneously and guide building back better.